Effects of Intranasal and Oral Bordetella bronchiseptica Vaccination on the Behavioral and Olfactory Capabilities of Detection Dogs - Amanda Collins; Rachel A. Bear; Amritha Mallikarjun; Sarah A. Kane; Jennifer L. Essler; Patricia Kaynaroglu; Rebecca Feuer; Jordan G. Smith; Cynthia M. Otto; Cynthia M. Otto (Frontiers in Veterinary Science, 2022)
The bacterium Bordetella bronchiseptica is responsible for serious respiratory disease in dogs, most often associated with ‘kennel cough’ (canine infectious tracheobronchitis). It is recommended that dogs are vaccinated against the bacterium every 6–12 months, either by oral or intranasal administration. Any impairment of dogs' olfactory capabilities due to medical treatments may impact their efficiency and accuracy in their jobs. This study examined (1) the effect of intranasal and oral vaccines on the olfactory capabilities of detection dogs; as well as (1) effects of the vaccines on canine behavior. Dogs that were vaccinated initially with the oral and 28 days later with intranasal B. bronchiseptica were generally slower to find the target odor than the dogs that were assigned intranasal then oral vaccine. This result prompted a second between-subjects study to further investigate any impact of intranasal administration of the B. bronchiseptica vaccine on the olfactory capabilities of dogs. The intranasal vaccine was of particular interest due to its prevalent use and potential for nasal inflammation leading to decreased olfactory capabilities. Neither odor threshold nor time spent searching for odor were affected by the intranasal vaccine. Behavioral analyses showed that behaviors associated with the dogs' positive and negative motivation affected their time spent finding the target odor; this suggests that behavior should be considered in future studies of olfactory performance.